Reducing Gun Violence Results from an Intervention in East Los Angeles - Tita, George (RAND Corporation, 2010)
To assess whether an initiative to reduce gun violence that had been successful in Boston could be adapted for use elsewhere, researchers selected an East Los Angeles area for a similar intervention that was to include both law enforcement and social service components. Although the latter component was not widely available when the intervention began, researchers found that the intervention helped reduce violent and gang crime in the targeted districts and that crime also decreased in surrounding communities.